1, makes the equality is true: 10 + 5 = 6 + 1; 5 = 5. Note: we can use any letter instead of the x (the most commonly used are x, y, z or t).Examples: 3 x = 7 is a linear equation with the unknown in x. 2, 7t = 4.8 is a linear equation with the unknown in t.x + 4 = 3 x + 7 is also a linear equation with the unknown x, that in addition, as we have seen, can be written, by simplification of the way 4 x = 3 another part, m x = 3 is not a linear equation, or first-degree, because the unknown x is elevated to the square. II. method the first thing we have to bear in mind is that an equation is an equality. For this reason, any change we make to the first member of the equation, we must also do it in the second member.

This means that if we add, subtract, divide or multiply a quantity to the first member, we must do the same in the second member. So we'll get that equality which is expressed in the equation remains true. In other words: we can add or subtract the same number on both sides of the equation without that why you change your solution; Thus, to + x = b is equivalent a: to + x to = (b), and which therefore also a: x = b; if we multiply or divide each Member of the equation by the same non-zero number, the solution of the equation does not change. Thus, ax = b is equivalent to and.To solve an equation just have to simplify algebraic expressions from both members to leave them in the form ax = b. read full information in solving equations of first degree original author and source of the article.

Posted by: |